Profile of School Partnership Collaboration Model with Parents to Support Educational Success at SD Terang Nusantara - Kristanti, Maria; Cahyani, Isah; Suhartono, Suhartono (Asian Journal of Social and Humanities, 2024)
This research delves into the school-parent partnership model at Terang Nusantara Elementary School in Bandung, to support educational success. Grounded in Ki Hadjar Dewantara's concept of the Education Tri-Center, this study highlights the importance of synergy between schools and parents in influencing students' academic achievement and character development. Employing qualitative methods, such as observation, interviews, and document analysis, this research reveals the dynamics of planning, implementation, and the impact of such partnerships. The results indicate that effective collaboration between schools and parents enhances academic performance and student-character development. This partnership is characterized by open communication and active participation from both parties. However, the study also identifies challenges, such as differing expectations, time constraints, and language and cultural barriers that impede the partnership. This research recommends strategies to overcome these obstacles, including improved communication, joint training, and adapting partnership activities to accommodate cultural diversity. The implications are the importance of schools recognizing and involving parents as strategic partners in the educational process.